The theories of the determinants of migration. What can we learn from the Scottish experience? / Baayah Baba - Baba, Baayah (Institute of Business Excellent (IBE), 2011)
There are many theories of migration. The human capital, search and the gravity models are among the most widely referred to by researchers. The influence of house prices, job vacancies, wage differentials on the migration decisions have widely been noted and have the expected signs. However, in a study done using the Scottish data the house price variables seem to give an opposite sign that contradicts previous findings. This could be due to the change in the determinants of migration whereby it is not just available house or accommodation that matters, it is something more than that. This finding could lead to further research on why there is a change in the determinants of migration in Scotland and what can Asians learn from the Scottish experience.